Morphological Structure of the Tongue of Gekko gecko in Yogyakarta, Indonesia - Aqiilah, Khairunnisa; Budipitojo, Teguh; Wijayanto, Hery; Budiariati, Vista; Pangestiningsih, Tri Wahyu; Ariana, Ariana; Saragih, Golda Rani; Kustiati, Ulayatul; Wihadmadyatami, Hevi (Journal of Tropical Biodiversity and Biotechnology, 2024)
Gekko gecko is a member of the order Squamata from the family Gekkonidae and mainly feeds on small insects. This study aims to determine the morphology of the tongue of Gekko gecko through Scanning Electron Microscopy (SEM), hematoxylin–eosin (HE) staining, and immunohistochemistry (IHC). Six adult Gekko gecko were obtained from the Special Region of Yogyakarta, and Gekko gecko tongue samples were stored in SEM fixative solution and then observed with SEM. For histochemical and IHC staining, tongue samples were processed into paraffin blocks and cut into 8 µm-thick sections. The SEM revealed three types of papillae: dome-shaped papillae at the apex, fan-shaped papillae at the corpus, and scale–like papillae at the radix. Histological observations showed that the tongue of the Gekko gecko was composed of tunica mucosa and tunica muscularis, and goblet cells were present in the lamina of the epithelial mucosa. Meanwhile, no taste buds were found. Immunoreactivity against PGP 9.5 was observed on the tunica muscularis of the apex, corpus, and radix. Taken together, this study provides new insight into the tongue morphology of Gekko gecko and is dominated by mechanical papillae on the tongue surface.